Why Libraries Should Retain a Core Print Reference Collection. Issue 4 (1st October 2016) - Lederer, Naomi
ABSTRACT: This article gives an overview of what reference material is and for what it is used. Desirable characteristics of print reference are described. Skills that are important for reference librarians are specifically and generally described throughout. Arguments on the importance of a core printed reference collection focus on convenience, cost, availability, online irritants, actual use of print, historical research, and future librarians' understanding of reference resources.